How Was Studied the Effect of Manual Wheelchair Configuration on Propulsion Biomechanics: A Systematic Review on Methodologies - Fritsch, Capucine; Poulet, Yoann; Bascou, Joseph; Thoreux, Patricia; Sauret, Christophe (Frontiers in Rehabilitation Sciences, 2022)
Background: For both sports and everyday use, finding the optimal manual wheelchair (MWC) configuration can improve a user’s propulsion biomechanics. Many studies have already investigated the effect of changes in MWC configuration but comparing their results is challenging due to the differences in experimental methodologies between articles. Purpose: The present systematic review aims at offering an in-depth analysis of the methodologies used to study the impact of MWC configuration on propulsion biomechanics, and ultimately providing the community with recommendations for future research. Methods: The reviewing process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart on two databases (Scopus and PubMed) in March 2022. Results: Forty-five articles were included, and the results highlighted the multiplicity of methodologies regarding different aspects of methodologies, including propulsion environment, experimental task, or measurement systems, for example. More importantly, descriptions of MWC configurations and their modifications differed significantly between studies and led to a lack of critical information in many cases. Discussion: Studying the effect of MWC configuration on propulsion requires recommendations that must be clarified: 1) the formalism chosen to describe MWC configuration (absolute or relative) should be consistent with the type of study conducted and should be documented enough to allow for switching to the other formalism; 2) the tested MWC characteristics and initial configuration, allowing the reproduction or comparison in future studies, should be properly reported; 3) the bias induced by the experimental situation on the measured data must be considered when drawing conclusions and therefore experimental conditions such as propulsion speed or the effect of the instrumentation should be reported. Conclusion: Overall, future studies will need standardization to be able to follow the listed recommendations, both to describe MWC configuration and mechanical properties in a clear way and to choose the experimental conditions best suited to their objectives.